Knowledge, attitude and practice regarding occupational protection against COVID-19 among midwives in China: A nationwide cross-sectional study. (September 2022) - He, Qiuyang; Wang, Guoyu; He, Jingjing; Wang, Yonghong; Zhang, Jinling; Luo, Biru; Chen, Peng; Luo, Xiaoju; Ren, Jianhua
Abstract: Midwives assume the roles in protecting perinatal women and newborns, meanwhile defending their own safety during the epidemic of COVID-19. Since there is currently no specific treatment available that targets the disease, strictly compliance with various infection prevention and control measures appears utmost important to achieve their occupational safety. We then explored the status quo and influencing factors of the knowledge, attitude and practice (KAP) of occupational protection against the COVID-19 among midwives in China. This online cross-sectional survey was conducted on 2663 midwives across the China during the early stages of the pandemic with a self-reported structured questionnaire. 97.4% and 92.9% of them were identified with positive attitude and appropriate practice, respectively, whereas only 6.4% showed good level of knowledge about the occupational protection toward the COVID-19. Midwives with older age, keeping on working during the breakout period, completing the training programs, caring the confirmed COVID-19 cases and having family members with cold-like symptoms were significantly associated with their KAP status. This study could provide valuable information not only for policy makers and administrators to optimize resource allocation and design education programs on targeted midwives, but also serve as a baseline for measuring changes in subsequent, post-intervention KAP studies.